(3bUjOI aj eOM GdfYfGYs - (3YHO GdhgGH Hf CMeO GOQGb,J (B1159 (3g` s
(3ChdgG (B:s
(3CdGgd ef GdCYTGH fHJ jhGab ehGabI GdfYfGY Hd hjWGHb s
(3BNQgG (B:s
(3aeGdi dG CKfi Ydjg hCYJfi HfXei dBdjg haVdc SGHb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B399 - (3U(B400s
(3Ydi GdeLehYI Jedc HGSe GdeNJGQ Hf YHO Gddg Hf CMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B182 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(505(3O(B) s
Keywords: (3GdWHs